The tax & legal playbook : game-changing solutions to your small business questions - Kohler, Mark J. (Entrepreneur Press, 2019)
Known for his candid works, Lawyers Are Liars, What Your CPA Isn't Telling You and The Business Owner's Guide to Financial Freedom, trusted advisor, CPA, and attorney Mark Kohler delivers again, giving conflicted business owners the go-to guide for confidently approaching legal and tax issues fundamental to protecting their business and themselves. Leveraging popular case studies, Kohler presents easy-to-grasp points supported by assessment quizzes, checklist, chapter summaries, and more.